2022
DOI: 10.1002/cpz1.462
|View full text |Cite
|
Sign up to set email alerts
|

Software Tool for Automatic Quantification of Sarcomere Length and Organization in Fixed and Live 2D and 3D Muscle Cell Cultures In Vitro

Abstract: Sarcomeres are the structural units of the contractile apparatus in cardiac and skeletal muscle cells. Changes in sarcomere characteristics are indicative of changes in the sarcomeric proteins and function during development and disease. Assessment of sarcomere length, alignment, and organization provides insight into disease and drug responses in striated muscle cells and models, ranging from cardiomyocytes and skeletal muscle cells derived from human pluripotent stem cells to adult muscle cells isolated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…MTs were compared in the absence (MToC, Video S1 , Figures 1 B and 3 A) or presence (VMToC, Figure 3 B) of an external vascular network. Sarcomere morphologies appeared similar in the MToC ( Figure 3 C) and VMToC ( Figure 3 D), which was confirmed by similar sarcomere lengths ( Figure 3 E) and alignment indices ( Figure 3 F) assessed using the SOTATool ( Stein et al., 2022 ). This indicated that there was no additional effect on sarcomere organization in the presence of external vascular network.…”
Section: Resultssupporting
confidence: 63%
“…MTs were compared in the absence (MToC, Video S1 , Figures 1 B and 3 A) or presence (VMToC, Figure 3 B) of an external vascular network. Sarcomere morphologies appeared similar in the MToC ( Figure 3 C) and VMToC ( Figure 3 D), which was confirmed by similar sarcomere lengths ( Figure 3 E) and alignment indices ( Figure 3 F) assessed using the SOTATool ( Stein et al., 2022 ). This indicated that there was no additional effect on sarcomere organization in the presence of external vascular network.…”
Section: Resultssupporting
confidence: 63%
“…Moreover, we observed that ACTA1 R256H/+ hPSC-CMs appear to have sarcomeric arrays that were less aligned with the longitudinal cell axis compared to WT. We quantified the alignment using SarcOmere Texture Analysis algorithm (SotaTool) which mathematically scores sarcomere alignment on a scale between 0 to 1, with higher alignment corresponding to a higher score (42). Consistent with our observations, WT cells had a significantly higher alignment score than ACTA1 R256H/+ hPSC-CMs ( Figure 5I ).…”
Section: Resultsmentioning
confidence: 99%
“…Immunofluorescence staining and measurement of sarcomere alignment. Immunostaining was performed similar to prior (38), but SotaTool was used to calculate sarcomere alignment (42). Details can be found in the supplemental methods.…”
Section: Methodsmentioning
confidence: 99%
“…Instead, the 4F+ Asns KD group exhibited significantly fewer cardiomyocytes staining for cell cycle markers Ki67, pH3, and Aurora kinase B (Figure 5N through 5P). At the same time, we adopted the software SotaTool 35 to compare the sarcomeric organization of cardiomyocytes between the 4F+ LacZ KD and 4F+ Asns KD groups. Each heart section was imaged at different representative regions with cardiomyocytes sectioned through the longitudinal axis, yielding 80 output results each (Figure S11B).…”
Section: Resultsmentioning
confidence: 99%